2020
DOI: 10.1128/mbio.02030-20
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies Microbial Fusion and Large-Scale Exchange of Cytoplasmic Proteins and RNA in a Syntrophic Clostridium Coculture

Abstract: Microbial syntrophy is universal in nature, profoundly affecting the composition and function of microbiomes. We have recently reported data suggesting direct cell-to-cell interactions leading to electron and material exchange between the two microbes in the syntrophy between Clostridium ljungdahlii and C. acetobutylicum. Here, transmission electron microscopy and electron tomography demonstrated cell wall and membrane fusions between the two organisms, whereby C. ljungdahlii appears to invade C. acetobutylicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(92 citation statements)
references
References 40 publications
3
86
2
Order By: Relevance
“…Among cells of the spirochaete Borrelia , frequent outer membrane fusion and occasional inner membrane fusion were observed [ 106 ]. A recent study reported complete interspecies cell–cell fusion with large-scale exchange of cellular components between the bacteria Clostridium ljungdahlii and Clostridium acetobutylicum [ 107 ].…”
Section: Forms Of Excitability In Eukaryotesmentioning
confidence: 99%
“…Among cells of the spirochaete Borrelia , frequent outer membrane fusion and occasional inner membrane fusion were observed [ 106 ]. A recent study reported complete interspecies cell–cell fusion with large-scale exchange of cellular components between the bacteria Clostridium ljungdahlii and Clostridium acetobutylicum [ 107 ].…”
Section: Forms Of Excitability In Eukaryotesmentioning
confidence: 99%
“…Here we describe the compositional dynamics and variation among microbial communities by a microbiome transition model. In this model, a microbial community is essentially a combination of microorganisms, and the structure of a community can be modified to another form by adding and/or removing species by compositional dispersal or fusion [8, 9] ( Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, since there is no standardized method for sample preparation for metatproteomic analysis, similar studies may yield varying results [ 51 , 52 ]. Furthermore, not all the detected microbial proteins may be present in the protein database being use for the identification [ 53 ] and this can limit the number of peptides identified in a given sample. Meanwhile, there are still many microbial proteins that have not been characterized and have no known functions [ 54 , 55 ] and this can make it difficult to make sense of such data during metaproteomic analysis.…”
Section: Omic Techniques In Gut Microbiome Studiesmentioning
confidence: 99%